EFFECT OF VARYING INCUBATION PERIODS ON CYTOTOXICITY AND VIRUCIDAL ACTIVITIES OF Justicia gendarussa Burm.f. LEAF EXTRACT ON HIV-INFECTED MOLT-4 CELLS - Widiyanti, Prihartini; Prajogo, Bambang; Widodo, Agustinus (African Journal of Infectious Diseases (AJID), 2018)
Backgrounds: Justicia gendarussa Burm.f. has an anti-HIV activity. This study was conducted to evaluate the effects of incubation periods on the cytotoxicity and virucidal activities of the J. gendarussa leaves extract on MOLT-4 cells.Materials and Methods: The cytotoxicity assay was evaluated by using the WST-1 test with incubation periods of 3 days and 5 days. The virucidal activity test was determined by measuring the inhibitory activities on the syncytium formation.Results: The cytotoxicity assay showed the value of CC50 on MOLT-4 cell culture with the test material of 70% ethanol extract of J. gendarussa leaves as much as 3928.620 μg /mL and 3176.581 μg /mL (incubation day 3 and day 5, respectively); fractionated-70% ethanol extract = 81782.428 μg /mL and 12175.870 μg/mL; and water extract = 16372.689 μg/mL and 2946.117 μg/mL. The test results of the virucidal activities (inhibit ≥ 90% the formation of syncytium) of 70% ethanol extract of J. gendarussa leaves is at a concentration 250 μg/mL, 500 μg/mL and 1000 μg/mL (3-day incubation) and 250 μg/mL (5-day incubation); and fractionated-70% ethanol extract at a concentration 250 μg /mL, 500 μg/mL and 1000 μg/mL (3-day incubation) and 1000 μg/mL (5-day incubation).Conclusion: 70% ethanol extract, fractionated-70% ethanol extract, and water extract of J. gendarussa leaves were relatively nontoxic toward MOLT-4 cells, and fractionated-70% ethanol extract had better potentials in virucidal activities.